An Emphasis on the Role of Long Non-Coding RNAs in Viral Gene Expression, Pathogenesis, and Innate Immunity in Viral Chicken Diseases - Anindita Sarma; Parul Suri; Megan Justice; Raja Angamuthu; Samuel Pushparaj (Non-Coding RNA)
The poultry farming industry encounters considerable obstacles stemming from viral diseases, resulting in elevated mortality rates and substantial economic losses. Current research highlights the significant involvement of long non-coding RNAs (lncRNAs) in the interactions between hosts and pathogens by enhancing antiviral responses at different levels, such as the activation of pathogen recognition receptors, as well as through epigenetic, transcriptional, and post-transcriptional modifications. Specific long non-coding RNAs (lncRNAs), including ERL lncRNA, linc-GALMD3, and loc107051710, have been recognized as significant contributors to the antiviral immune response to multiple avian viral pathogens. Understanding the mechanisms by which long non-coding RNAs (lncRNAs) act offers valuable insights into prospective diagnostic and therapeutic approaches aimed at improving disease resistance in poultry. Differentially expressed lncRNAs may also be utilized as biomarkers for both prognosis and diagnosis of avian viral diseases. This review delves into the various roles of long non-coding RNAs (lncRNAs) in the context of viral diseases in chickens, such as avian leukosis, Marek’s disease, infectious bursal disease, avian influenza, infectious bronchitis, and Newcastle disease. It highlights the pivotal role of lncRNAs in the complex dynamics between the host and viral pathogens, particularly their interactions with specific viral proteins. Understanding these interactions may provide valuable insights into the spatial and temporal regulation of lncRNAs, aid in the identification of potential drug targets, and reveal the expression patterns of lncRNA and coding gene transcripts in response to different viral infections in avian species.